Climate Smart Agriculture in the African Context - Williams, Timothy O.; Mul, Marloes L.; Cofie, Olufunke O.; Kinyangi, James; Zougmoré, Robert B.; Wamukoya, George; Nyasimi, Mary; Mapfumo, Paul; Speranza, Chinwe Ifejika; Amwata, D.; Frid-Nielsen, Snorre; Partey, Samuel T.; et al. (2015)
Agriculture remains vital to the economy of most African countries and its development has significant implications for food security and poverty reduction in the region. Increase in agricultural production over the past decades has mainly been due to land area expansion, with very little change in production techniques and limited improvement in yields. Currently one in four people remains malnourished in Africa. CSA integrates all three dimensions of sustainable development and is aimed at (1) sustainably increasing agricultural productivity and incomes; (2) adapting and building resilience to climate change from the farm to national levels; and (3) developing opportunities to reduce greenhouse gas emissions from agriculture compared with past trends. It is an approach to identify the most suitable strategies according to national and local priorities and conditions to meet these three objectives. There is no such thing as an agricultural practice that is climate smart per se. Whether or not a particular practice or production system is climate smart depends upon the particular local climatic, biophysical, socio-economic and development context, which determines how far a particular practice or system can deliver on productivity increase, resilience and mitigation benefits. For Africa to reap the potential benefits CSA, concrete actions must be taken to: enhance the evidence base to underpin strategic choices, promote and facilitate wider adoption by farmers of appropriate technologies; develop institutional arrangements to support, apply and scale-out CSA from the farm level to the agricultural landscape level; manage tradeoffs in perspectives of farmers and policymakers; strengthen technical, analytical and implementation capacities; ensure policy frameworks and public investments are supportive of CSA; develop and implement effective risk-sharing schemes.